2019
DOI: 10.1016/j.optcom.2019.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Performance-enhanced NOMA-VLC using subcarrier pairwise coding

Abstract: To alleviate the error propagation issue of non-orthogonal multiple access (NOMA) based visible light communication (VLC) systems, we propose and experimentally demonstrate the subcarrier pairwise coding (PWC) based NOMA-VLC. Without extra coding overhead, the computation-efficient subcarrier PWC can significantly improve the overall system performance by pairing the subcarriers of high signal-to-noise ratios (SNRs) with those of low SNRs. Under different transmitted baud rate from 150 MSa/s to 225 MSa/s, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The above investigations show that most EP mitigation approaches in NOMA-VLC systems are designed for QAM [36,37] or OFDM [38] . Given that VLC prefers Intensity Modulation and Direct Detection (IM/DD), pulse modulation schemes, such as OOK, pulse position modulation, and pulse width modulation, attract considerable attention and are widely implemented in VLC systems because of its low cost and simplicity [40,41] .…”
Section: Motivation and Contributionmentioning
confidence: 92%
See 1 more Smart Citation
“…The above investigations show that most EP mitigation approaches in NOMA-VLC systems are designed for QAM [36,37] or OFDM [38] . Given that VLC prefers Intensity Modulation and Direct Detection (IM/DD), pulse modulation schemes, such as OOK, pulse position modulation, and pulse width modulation, attract considerable attention and are widely implemented in VLC systems because of its low cost and simplicity [40,41] .…”
Section: Motivation and Contributionmentioning
confidence: 92%
“…In Ref. [38], Shi et al proposed the subcarrier pairwise coding scheme in NOMA-VLC systems with OFDM adopted. This scheme was experimentally demonstrated, and the corresponding results showed that the system performance can be remarkably improved.…”
Section: Related Workmentioning
confidence: 99%
“…In 2019, C. Chen et al reported a SIC-free NOMA-VLC using constellation partitioning coding with transmission distance of 100 cm and UE offset of 10 cm [16]. J. Shi et al demonstrated a NOMA-VLC using subcarrier pair-wise coding with transmission distance of 40 cm [17]. In the same year, H. Li et al illustrated a NOMA-VLC using pre-distorted layered asymmetrically clipped OFDM with transmission distances of 40 cm and 70 cm for UE 1 and UE 2 respectively [18].…”
Section: Introductionmentioning
confidence: 99%